Isotopic effects in elastic and inelastic 12,13C + 16,18O scattering - A. T. Rudchik; Yu. O. Shyrma; E. I. Koshchy; S. Kliczewski; B. G. Novatsky; O. A. Ponkratenko; E. Piasecki; G. P. Romanyshyna; K. Rusek; Yu. M. Stepanenko; I. Strojek; S. B. Sakuta; et al. (Ядерна фізика та енергетика)
New angular-distribution data of 13С + 18О elastic and inelastic scattering at the energy Elab(18O) = 105 MeV were obtained for the transitions to the ground and excited states 3.088 MeV(1/2+), 3.555 MeV (1/2-), 3.854 MeV (5/2+) of 13С and 1.982 MeV (2+), 3.555 MeV (4+), 3.921 MeV (2+), 4.456 MeV (1-), 5.098 MeV (3-), 5.260 MeV (2+) of 18O. These and the 13С + 18О elastic scattering data taken from the literature at the energies Elab(18O) = 15, 20, 24, 31 MeV and Elab(13С) = 24 MeV were analysed within the optical model and coupled-reaction-channels methods. Sets of 13С + 18О optical potential parameters and their energy dependence were obtained. Contributions of potential scattering and transfer reactions to the elastic and inelastic channels of 13С + 18О scattering were studied. Isotopic differences (effects) in 12, 13С + 16, 18О optical potential parameters were investigated.